Drivers of Celebrity Endorsement and Its Effect on Consumer’s Buying Behavior: A Case Study of FMCGs in Peshawar - SHAHZAD KHAN; SAQIB SHAHZAD; NAUMAN HABIB; GHAYYUR QADIR (Journal of Business & Tourism, 2021)
Because of a business environment of cut-throat competition, companies must find ways to strike for survival and sustain a competitive position in the market. Celebrity endorsement is one of the strategies which companies frequently used to promote the brand thus enhance sales and ultimately increase market share. There are a number of researches which investigated the effects of celerity endorsement on consumers’ buying behavior. However, traits such as credibility, expertise attractiveness and compatibility of celebrity endorsers have not been investigated. Therefore, this research is to investigate effects of celebrity endorsement on consumers’ buying behavior. In order to obtain a more reliable result, a quantitative research is carried out to investigate the topic. In general it was found that which trait of a celebrity is most significant in influencing consumer buying behavior. For instance the credibility, expertise, attractiveness and compatibility of the endorser were found to be the most important traits of the celebrity that can influence consumer buying behavior. Generally the effect of celebrity endorsement is found to have little direct impact on consumers’ purchase decision, yet it is still an effective strategy because it is suggested as a good way to grab consumers’ attention. This research also suggests some criteria for selecting the celebrity endorsers with the right attributes for their products. Therefore companies are recommended to conduct sufficient research in order to generate the best effect of a celebrity endorsement.